Holistic understanding of the response of grapevines to foliar application of seaweed extracts - Zarraonaindia, Iratxe; Cretazzo, Enrico; Mena-Petite, Amaia; Díez-Navajas, Ana M.; Pérez-López, Usue; Lacuesta, Maite; Pérez-Álvarez, Eva Pilar; Puertas, Belén; Fernandez-Diaz, Catalina; Bertazzon, Nadia; Cantos-Villar, Emma (Frontiers in Plant Science, 2023)
Viticulture is highly dependent on phytochemicals to maintain good vineyard health. However, to reduce their accumulation in the environment, green regulations are driving the development of eco-friendly strategies. In this respect, seaweeds have proven to be one of the marine resources with the highest potential as plant protective agents, representing an environmentally-friendly alternative approach for sustainable wine production. The current work follows an interdisciplinary framework to evaluate the capacity of Ulva ohnoi and Rugulopteryx okamurae seaweeds to induce defense mechanisms in grapevine plants. To our knowledge, this is the first study to evaluate Rugulopteryx okamurae as a biostimulator. This macroalgae is relevant since it is an invasive species on the Atlantic and Mediterranean coast causing incalculable economic and environmental burdens. Four extracts (UL1, UL2, RU1 and RU2 developed from Ulva and Rugulopteryx, respectively) were foliar applied to Tempranillo plants cultivated under greenhouse conditions. UL1 and RU2 stood out for their capacity to induce defense genes, such as a PR10, PAL, STS48 and GST1, mainly 24 hours after the first application. The increased expression level of these genes agreed with i) an increase in trans-piceid and trans-resveratrol content, mainly in the RU2 treated leaves, and, ii) an increase in jasmonic acid and decrease in salicylic acid. Moreover, an induction of the activity of the antioxidant enzymes was observed at the end of the experiment, with an increase in superoxide dismutase and catalase in the RU2-treated leaves in particular. Interestingly, while foliar fungal diversity was not influenced by the treatments, alga extract amendment modified fungal composition, RU2 application enriching the content of various groups known for their biocontrol activity. Overall, the results evidenced the capacity of Rugulopteryx okamurae for grapevine biostimulation, inducing the activation of several secondary metabolite pathways and promoting the abundance of beneficial microbiota involved in grapevine protection. While further studies are needed to unravel the bioactive compound(s) involved, including conducting field experiments etc., the current findings are the first steps towards the inclusion of Rugulopteryx okamurae in a circular scheme that would reduce its accumulation on the coast and benefit the viticulture sector at the same time.